Reduction of Fe(ii) and Zn(ii) using fresh eichhornia crassipes - Mohd Saifulnizam, Awang Jaafar (2010)
The high content of Iron(Fe) and Zinc(Zn) in the wastewater become one of the major problem to the industry because the they will contaminate the environment and furthermore the ecosystem. The ability of Eichhornia Crassipes as a heavy metal removal is investigated in this research. The objective of this research is to remove Fe(II) and Zn(II) from aqueous solution and to investigate the potential of Eichhornia Crassipes for reduction of Fe(II) and Zn(II). The fresh Eichhornia Crassipes is obtained from local lake in Gambang,Pahang. This research was run based on three parameter. These parameter are contact time, adsorbent dosage and pH. The absorbance of each parameter was analyzing using Ultraviolet-visible Spectroscopy. This research was run at various contact times such as 1 day, 2 day, 3 day, 4 day and 5 day. For effect of adsorbent dosage, different amount of adsorbent was use to absorb the heavy metal. This also applies to the effect of pH. Various value of pH in each aqueous solution was used. It was found out that, increasing the contact time will increase the removal Fe(II) and Zn(II) from aqueous solution. Increasing the number of plant also will increase the reduction of Fe(II)and Zn(II). Based on the data acquire, the Fe(II) and Zn(II) can be totally remove. This research also found out that Eichhornia Crassipes can remove Fe(II) from industrial wastewater up to 80 % removal